Altmetrics: alternative librarians or librarians´ alternative - González-Fernández-Villavicencio, Nieves (Anuario ThinkEPI, 2015)
In recent years academic librarians have focussed their activities on supporting researchers in various aspects of their scientific activity. In this scenario of support for research and bibliometric studies, librarians increasingly need to know, test, experiment with, use and disseminate altmetrics (alternative metrics). A review of altmetrics indicators is presented, and the role of librarians is considered, particularly university librarians, who should be active and engaged in this area. Steps that librarians should take to incorporate almetrics into their daily work routine are proposed.